Rendimiento de aserrío de la especie Guarea guidonia (Requia) en la empresa Consorcio Forestal Loreto S.A.C, Iquitos, Loreto–2022 - Armas Salas, Frank Edson (2023)
The present study was carried out in the wood transformation plant of the company CONSORCIO `` LORETO S.A.C, owned by Engineer Willian Castro located on the Iquitos Nauta Km 2.5 highway, with the purpose of determining the yield of the Guarea Guidonia (requia) species in depending on the quality of the log and the type of sawn Wood. From the results obtained, it can be seen that 49 logs were used for the yield study, which added a total of 43.85 m³, the average per log was 0.90 m³, with quality A and quality B logs. The first quality logs were a total of 40 logs with 36.35 m³ with diameters ranging from 0.42 m of mínimum diameter to 0.67 m of máximum diameter, with the average being 0.53m and the measurement of the fashion diameter of the logs of 0.52 cm. The second quality logs were only 9 out of a total of 49 with a volumen of 7.50 m³ and an average per log 0f 83 m³. The yield of the relationship between the total relationship between the total volue in sawing and the total gross volume was 83%. The yield of the relationship between the total volume in sawing and the total volume of the commercial long species was 90.73 %. The yield of the relationship between the total volume in sawing and the total volumen of long narrow raw wood was 9.28%.